Overcoming of low discharge problem in shallow well jet pump through the application of total quality function deployment. (2018) - Sivasamy, K.; Arumugam, C.; Devadasan, S.R.; Murugesh, R.; Arun, K.K.; Senthilkumar, K.M.
A research which was carried out to investigate the application of a technique called total quality function deployment (TQFD) in the case of overcoming low discharge problem in a type of pump known as shallow well jet pump has been reported in this paper. TQFD is incorporated with five matrices for translating customers' vague languages into practical languages. In the research reported in this paper, all the five matrices of TQFD were developed. When developing component deployment matrix, computational fluid dynamics (CFD) was used to determine the optimum design of nozzle and venture. The prototypes with optimum design were developed by using a rapid prototyping technology machine. These prototypes were fitted in a shallow well jet pump. On testing, this pump was found to deliver maximum discharge. Thus TQFD was employed to translate the customers' vague language into technical language.